Analysis of sphingosine 1-phosphate receptors involved in constriction of isolated cerebral arteries with receptor null mice and pharmacological tools - Salomone, S (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Sphingosine 1-phosphate (S1P) selectively and potently constricts isolated cerebral arteries, but this response has not been pharmacologically characterized. EXPERIMENTAL APPROACH: The receptor subtype(s) involved in S1P-induced cerebrovascular constriction were characterized using genetic (S1P(2) and S1P(3) receptor null mice) and pharmacological tools (phospho-FTY720, a S1P(1/3/4/5) receptor agonist; SEW2871, a S1P(1) receptor agonist, JTE-013, a S1P(2) receptor antagonist, VPC23019, a S1P(1/3) receptor antagonist). Isolated basilar or peripheral (femoral, mesenteric resistance) arteries, from either rat or mouse, were studied in a wire myograph. KEY RESULTS: S1P concentration-dependently constricted basilar artery in rat, wild-type (WT) and S1P(2) null mice, but barely affected vascular tone in S1P(3) null mice. Vasoconstriction to U46619 (a thromboxane analogue) or to endothelin-1 did not differ between WT, S1P(2) and S1P(3) null mice. JTE-013 inhibited not only S1P-induced vasoconstriction, but also KCl-, U46619- and endothelin-1-induced constriction. This effect was observed in WT as well as in S1P(2) null mice. VPC23019 increased the concentration-dependent vasoconstriction to S1P in both rat and mouse basilar arteries with intact endothelium, but not in rat basilar artery without endothelium. Phospho-FTY720 concentration-dependently constricted rat basilar arteries, but not femoral or mesenteric resistance arteries, while SEW2871 did not induce any response in the same arteries. CONCLUSIONS AND IMPLICATIONS: S1P constricts cerebral arteries through S1P(3) receptors. The purported S1P(2) receptor antagonist JTE-013 does not appear to be selective, at least in rodents. Enhancement of S1P-induced contraction by VPC23019 might be related to blockade of S1P(1) receptors and NO generation.